2005
DOI: 10.4321/s0212-71992005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento del tromboembolismo pulmonar agudo con heparina de bajo peso molecular subcutánea: Comparación con heparina no fracionada intravenosa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Treatment monitoring enables the determination of the most appropriate therapy to achieve a clinical response in the absence of titration. Clopidogrel is widely used to prevent the onset or recurrence of thromboembolism in cats with HCM [7]. A previous study reported that clopidogrel at a total dose of 18.75 mg/cat significantly decreased platelet aggregation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment monitoring enables the determination of the most appropriate therapy to achieve a clinical response in the absence of titration. Clopidogrel is widely used to prevent the onset or recurrence of thromboembolism in cats with HCM [7]. A previous study reported that clopidogrel at a total dose of 18.75 mg/cat significantly decreased platelet aggregation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%